Nutritional needs. - Falen, Juan (2015)
In recent decades it has been emphasized about the dangers to the mother and the fruit conceptional restricting weight gain to figures ranging between 45 and 7.0 1.2 kg during pregnancy. On the other hand, it has been shown that increased maternal weight and pre-pregnancy weight are two factors that significantly influence the birth weight. In turn, the birth weight is important, because we have seen that has an impact on neonatal morbidity and mortality.